3D Laser Scanning representation in Architecture - Bernadette Marie Devilat; Felipe Andres Lanuza (Architecture Image Studies Scientific Journal)
In Architecture, representing the context is for both a technical need and an understanding process for architectural discipline. The creation of drawings is not only to measure and represent reality to intervene in it but also to analyse it in a broader sense, and often for purposes beyond placing a future design. From a wide range of available 3D recording technologies, we have developed our work using 3D laser scanning, also known as LiDAR. This method can provide comprehensive, detailed and accurate datasets to create architectural visualisations that offer new technical capabilities and conceptual dimensions of site, context and place. This essay shows a series of explorations and applications selected from our last 12 years of research and practice, ranging from documenting built heritage at risk to using the record as a basis for design. These are grouped thematically to reflect on their challenges and possibilities for architectural design and representation.